Evaluation of [(13)C]Urea Breath Test and Helicobacter pylori Stool Antigen Test for Diagnosis of H. pylori Infection in Children from a Developing Country - Cardinali, Luciana de Carvalho Costa (American Society for Microbiology, 2003)
The [(13)C]urea breath test ((13)C-UBT) and Helicobacter pylori stool antigen test (HpSA) for the diagnosis of H. pylori infection in children were validated. The sensitivity, specificity, and positive and negative predictive values were 93.8, 99.1, 97.8, and 98.0%, respectively, for the (13)C-UBT and 96.9, 100, 100, and 98.0%, respectively, for HpSA. Both tests are appropriate for diagnosing H. pylori infection in children.